Moral Hazard and International Crisis Lending : A Test - Dell'Ariccia, Giovanni (IMF Working Papers; Working Paper ;, 2002)
We test for the existence of a moral hazard effect attributable to official crisis lending by analyzing the evolution of sovereign bond spreads in emerging markets before and after the Russian crisis. The nonbailout of Russia in August 1998 is interpreted as an event that decreased the perceived probability of future crisis lending to emerging markets. In the presence of moral hazard, such an event should raise not only the level of spreads, but also the sensitivity with which spreads reflect fundamentals as well as their cross-country dispersion. We find strong evidence for all three effects.